YOUTH THEATRE ART NON-FORMAL EDUCATION IN THE CONTEXT OF DRAMA PEDAGOGY HISTORICAL DEVELOPMENT - Kļava, Oskars; Katane, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Nowadays not only formal but also non-formal education plays a significant role in the context of lifelong learning. By getting involved in various non-formal education activities, with overall and personality development, children and young people socialise, gain new experiences, and acquire new social roles. The wider the spectrum of non-formal education activities, the more possibilities there are for each child and young person to find the most suitable to get involved in according to their interests, needs, abilities, future intentions and goals. One of the forms of non-formal education for children and youth is theatre art non-formal education, which finds its theoretical methodological base in drama pedagogy. School drama clubs, optional course of public speech, drama studio etc. have a significant role and contribute to the promotion of students’ personality development and socialisation. The aim of this article is to give a theoretical justification of the youth theatre art non-formal education in the context of drama pedagogy historical development. The approaches, principles, new methods of drama pedagogy were and are currently used by teachers-practitioners in many countries not only in the drama non-formal education but also throughout formal education – by including drama elements as learning techniques and methods across different subjects, thus making the drama pedagogy universal, constantly present everywhere and at all times.